Actul normativ și actul juridic individual [Articol] - Negru, Andrei (CEP USM, 2021)
The correlation between the legal normative act and the individual legal act, at first sight, would be a quite frequently approached topic and would present a predominantly didactic interest and not a theoretical-practical one. Contemporary legal reality shows that the applicative interest and the impact on the mechanisms of protection of human rights, freedoms and public interests, in an area of good governance, ensured by the rule of law, manifested by the correlation and the clear determination in the legal doctrine of the correlation between the normative act and the individual legal act, obtains a new approach of an accentuated relevance. The clear appreciation of the normative or individual nature of the legal act develops the perspective of carrying out the judicial control of their constitutionality or legality, of the preliminary procedures necessary to be applied in exercising different forms of control, of the consequences of pronouncing a decision by a court and of issues generated by the enforcement of this decision. In these conditions, an elementary doctrinal subject obtains the status of an important field of theoretical - practical investigation, oriented towards the streamlining of the act of justice and to the observance of legality.
THE NORMATIVE ACT AND THE INDIVIDUAL LEGAL ACT
Keywords: normative legal act; individual legal act; administrative procedure; independence of the judicial authority; Constitutional Court; human rights; interference in the judicial activity